A geographical study of the New Zealand textile manufacturing industry, with particular reference to the Wellington region - Vickery, Evan Wakefield (Massey University, 1975)
This thesis is a study of the New Zealand textile manufacturing industry and its components. It investigates the nature of location patterns, the changes within the components of the industry and the changes in industrial organisation which have occurred since 1950. The location of factories engaged in manufacturing textiles is detailed, shifts in components of the industry are analysed and early location factors in the industry are discussed. It is argued that technological advances in various facets of the industry have been influential in determining the present day location of the factories in the industry. The impact of technology and its requirements within the industry are examined specifically in terms of process product and organisational adjustments. The resulting developments, particularly the form of intra- and inter- industry linkages are outlined. In addition the form of industry intra-urban linkages are explored with particular reference to the Wellington Region.
Keywords: Textile industry; New Zealand -- Wellington (Region)